PENENTUAN STRATEGI BAURAN PEMASARAN PELUMAS FOOD GRADE GREASE BERBAHAN DASAR KELAPA SAWIT DI KABUPATEN PURBALINGGA - Tri Yanto; Aiman Abulkhair (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The  objective  of  this  study  is  to  determine  the  merchant  and  the  user preferences  to  the  specification  lubricating  grease  lubricants,  color  lubricants, package  sizes,  shape  packaging  labels,  distribution  of  lubricants,  promotion,  and price. Sampling using purposive sampling technique. Analysis of data using friedman test  with  5%  error  level.  If  there  are  differences  then  test ed  further  by  LSD.  The results  of  this  research  note  that  lubricant  specifications  preferred  by  merchants, which is preferred by the user while the grease is food grade lubricants and general machinery lubrication; the color lubricant preferred by merchantsis natural and blue, which  is  preferred  by  the  user  while  the  grease  is  the  natural  color;  pack  sizespreferred by merchants is size 350 g and 150 g with packing cup and bulk, while users liked  the  size  of  350  g  with  packing  cup;  form  label  lubricants  are  preferred  by merchants grease a round shape that is labeled with red and green as well as a square shape label in red, while the grease is preferred by the user labels round and square shapes  in red;  lubricants  distribution  are  preferred by  merchants  grease ie grocery stores, retail stores, repair shops,  and peddlers, while the grease is preferred by the user  distribution  through  grocery  stores  and  workshops;  lubricants  promotion  are preferred by merchants grease is through internet media, banners, brochures, radio and posters, while users of grease liked  by  media promotion banners, brochures and posters;  the price lubricant grease favored by  merchants  as preferred by the user of grease that low price low quality, medium quality and medium price high price of high quality.